The correlation between students' reading and listening score in a standardized test of TOEFL - Mega Safitri; Anik Nunuk Wulyani; Suharyadi Suharyadi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
This study aimed at analyzing the correlation between reading and listening in TOEFL ITP test and how much reading predicts listening. It involved 50,684 reading and listening scores in 2015-2019 test periods of undergraduate students in one of the state universities in Malang. The data were collected by using standardized TOEFL ITP issued by ETS. Using Pearson Correlation Product Moment and linear regression analysis, the result demonstrated reading and listening had significant, linear, and strong correlation (.682), and reading significantly predicted 46.5% variance of listening. The results lead to the hypothesis that two language input skills, reading and listening significantly correlated and predicted one another. The result also suggested that correlation language skills not only occurred among reading and writing and listening and speaking, but also it happened in reading and listening. Moreover, the results suggested the combination of reading and listening activities in classroom activities.